(untitled) (Bangladesh Journal of Child Health, 2021)
Background: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy.There are many successful treatment regimens for ALL. The chemotherapeutic agents used in the treatment of ALL are potentially hepatotoxic. Ursodeoxycholic acid (UDCA) has some role in preventing chemotherapy induced hepatotoxicity. The study was done to find out the hepatoprotective efficacy of UDCA in childhood ALL. Materials &Methods: This was a quasi-experimental study conducted in the department of Paediatric Haematology and Oncology, Dhaka Medical College Hospital, Dhaka. A total of 35 patients diagnosed as ALL were randomized in two groups.One group got UDCA along with chemotherapy and the other group chemotherapy alone. Estimation of S. ALT, S. AST and S. bilirubin were done before and after 1st,2nd,3rd and 4th week of starting chemotherapy. Result: The mean levels of S. ALT and S. AST were higher in the group that did not get UDCA. There were significant differences between S. ALT and S. AST level after 4th weeks of starting chemotherapy. However, S. bilirubin level was almost similar in both groups. Conclusion: UDCA showed hepatoprotective efficacy in induction period of chemotherapy. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 29-33